2015
DOI: 10.1002/cphc.201500103
|View full text |Cite
|
Sign up to set email alerts
|

Fe K‐Edge X‐ray Absorption Fine Structure Determination of γ‐Al2O3‐Supported Iron‐Oxide Species

Abstract: The structure of FeOx species supported on γ-Al2 O3 was investigated by using Fe K-edge X-ray absorption fine structure (XAFS) and X-ray diffraction (XRD) measurements. The samples were prepared through the impregnation of iron nitrate on Al2 O3 and co-gelation of aluminum and iron sulfates. The dependence of the XRD patterns on Fe loading revealed the formation of α-Fe2 O3 particles at an Fe loading of above 10 wt %, whereas the formation of iron-oxide crystals was not observed at Fe loadings of less than 9.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 27 publications
6
18
0
Order By: Relevance
“…6 For 15 Fe/Al 2 O 3 , a satellite peak at 650 °C was observed which may be due to the formation of a minority 3D-Fe 2 O 3 species due to the higher coverage. 30,50,51 This is consistent with XAS results presented in section 3.3, which indicates some agglomeration at higher Fe loading. From Figure 5b, it is observed that the peak temperature (Tp) of the supported Fe oxide species appears to be relatively independent of Fe loading over Al 2 O 3 .…”
Section: X-ray Absorption Spectroscopysupporting
confidence: 91%
See 3 more Smart Citations
“…6 For 15 Fe/Al 2 O 3 , a satellite peak at 650 °C was observed which may be due to the formation of a minority 3D-Fe 2 O 3 species due to the higher coverage. 30,50,51 This is consistent with XAS results presented in section 3.3, which indicates some agglomeration at higher Fe loading. From Figure 5b, it is observed that the peak temperature (Tp) of the supported Fe oxide species appears to be relatively independent of Fe loading over Al 2 O 3 .…”
Section: X-ray Absorption Spectroscopysupporting
confidence: 91%
“…Similarly, other studies also suggested that iron can be dispersed between 4 and 5.5 Fe atoms nm −2 over γ-Al 2 O 3 support. 30,51 Accordingly, the XRD and PDF results in this work indicate the possibility of forming a highly dispersed Fe-phase. Notably, temperatures higher than 1000 °C are usually required to form aluminate spinel (FeAlO 3 ) or crystalline hercynite (FeAl 2 O 4 ) from Fe 2 O 3 and Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…FeO x in the above case, forms various structures depending on its loading amount. 28 The structural variation of modifying species is expected to change catalytic activity of its supported metal catalysts. Actually, Tomita et al demonstrated that the variation of FeO x on Al 2 O 3 with the Fe loading significantly affects the catalytic activity of its supported Pt nanoparticles for CO oxidation reaction.…”
Section: ■ Introductionmentioning
confidence: 99%